Intracellular Survival of Staphylococcus aureus in Endothelial Cells: A Matter of Growth or Persistence - Rollin, Guillaume; Tan, Xin; Tros, Fabiola; Dupuis, Marion; Nassif, Xavier; Charbit, Alain; Coureuil, Mathieu (Frontiers in Microbiology, 2017)
The Gram-positive human pathogen Staphylococcus aureus is a leading cause of severe bacterial infections. Recent studies have shown that various cell types could readily internalize S. aureus and infected cells have been proposed to serve as vehicle for the systemic dissemination of the pathogen. Here we focused on the intracellular behavior of the Community-Associated Methicillin-Resistant S. aureus strain USA300. Supporting earlier observations, we found that wild-type S. aureus strain USA300 persisted for longer period within endothelial cells than within macrophages and that a mutant displaying the small colony variant phenotype (∆hemDBL) had increased intracellular persistence. Time-lapse microscopy revealed that initial persistence of wild-type bacteria in endothelial cells corresponded to distinct single cell events, ranging from active intracellular bacterial proliferation, leading to cell lysis, to non-replicating bacterial persistence even one week after infection. In sharp contrast, ∆hemDBL mutant bacteria were essentially non-replicating up to ten days after infection. These findings suggest that internalization of S. aureus in endothelial cells triggers its persistence and support the notion that endothelial cells might constitute an intracellular persistence niche responsible for reported relapse of infection after antibiotic therapy.